Experimental Confirmation of Avogadros Law for Thermal Radiation - Ivanov, Mikhail Jakovlevich; Mamaev, Vadim Konstantinovich; Tsvetkov, Igor Viktorovich; Zhestkov, Grigoriy Borisovich (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Experimental study of pressure variation in metal empty sealed container in low vacuum conditions (0.1-10 mbar) for temperature range from 290 to 1490 K is presented. Three characteristic areas of pressure variation were registered: the pressure growth in accordance with Avogadros law in the temperature range from 290 to 700-800 K, the pressure drop in the temperature range from 800 to 1300 K and again the intensive pressure increasing in the temperature range from 1300 to 1490 K. Possible causes of registered pressure variation in sealed container with increasing temperature and then cooling to its original conditions were analyzed. One of the more active causes is thermal radiation action in metal empty sealed container.